Student Perception Review from Gender: Electronic Moduls of Mathematical Physics - Tanti, Tanti; Astalini, Astalini; Darmaji, Darmaji; Kurniawan, Dwi Agus; Fitriani, Riska (Jurnal Pendidikan Indonesia, 2022)
The role of technology that continues to develop in the era of globalization, especially in the field of education, demands various innovations in the teaching and learning process to improve the quality of learning in the world of education. However, in learning, some students have negative perceptions that can make students not enthusiastic about participating in learning. Students will have difficulty understanding the material and will impact less than optimal learning outcomes of mathematics and physics in learning. This study examines the differences in students' perceptions based on gender in grades A and B in the physics-mathematics e-module. This type of research is quantitative and is conducted by a survey. The data collection instrument is a perception survey using a Likert scale. Data were analyzed descriptively (mean, median, mode, frequency, and percent) and inferential statistics (hypothesis test: normality and homogeneity tests, and hypothesis tests: independent T-test). Technique The sample is a total sample of 80 students from 2 classes. The result of this research is that there is a significant difference between female students' perceptions with a significance level of 0.049 and a significance level of 0.005 for boys. The key is that the average difference in perception between women and men is lower. Men are more rational in inserting something, while women are more emotional. The results of this study are expected to contribute to educators in improving the quality of learning in an educational institution.